Threads, Woven Together: Negotiating the Complex Intersectionality of Writing Centres - Srividya Natarajan; Patrick Morley (Discourse and Writing/Rédactologie, 2020)
The Canadian college where the authors are employed has an ethos that supports its writing centre’s commitment to promoting equitable access to power, education, and employment. In recent years, one result of this ongoing commitment has been the hiring of tutoring staff with diverse identities and life-situations (in terms of race and ethnicity, dis/ability, and sexuality). The authors of this paper, one of them the director of the centre and the other a consultant at the centre, draw on their personal experiences and observations to discuss one unexpected consequence of the push for inclusivity: tutees sometimes struggle to process the demand for social literacy and cross-cultural competence placed on them during encounters with tutors who have non-mainstream identities or affiliations. Seeking to understand the pedagogic and ethical complexities of encounters specifically between tutees and racialized tutors, we propose that responsibility for effecting positive social change—for building a “brave space”—through patient relationship-building and commitment to critical consciousness be allocated to the writer and the tutor, but above all to the writing centre as a collective.